Opportunities for feeding forages to pigs in Uganda - Maass, Brigitte L.; Kabirizi, J.M.; Pezo, Danilo A.; Carter, N.; Ouma, Emily A.; Zziwa, Emmanuel; Chiuri, Wanjiku L. (International Center for Tropical Agriculture, 2014)
Pigs can play an important role in risk diversification and livelihood security of many smallholder and poor households in Uganda. Women and youth/children provide most of the pigproduction labour, especially for forage collection, feeding and watering; and they are responsible for about 90% of pigs produced in Uganda. In the smallholder production systems practised both in rural and peri-urban areas, a variety of forage species are traditionally used for pig feeding, the majority of them being gathered for several hours every day. Overall, there is an overreliance on feeding crop residues, ‘weeds’ and forages both through collection and scavenging/ tethering, usually not meeting the nutritional requirements of pigs, which results in slow growth rates. Data on feeding pigs in Uganda were collected during focus group discussions and key informant interviews in three districts, Masaka, Mukono and Kamuli, during the years 2013–2014. In Uganda, there has been generally limited research on pigs and pig systems, while forage research has traditionally focused on feeding ruminants. A comprehensive literature review on feeding forages to pigs in the tropics revealed that it is mainly animal nutritionists who concern themselves with nutritional effects of forages on the animals and their suitability as pig feeds; aspects of integrating cultivated forages into crop-livestock production systems, labour requirements, gender issues, and economic returns are essentially not considered. Despite the widely recognised constraint of insufficient animal feeds, especially during dry seasons, adoption of cultivated forages in the tropics has been generally slow, and hindering factors have not been fully understood. Some cultivated forages show nutritional attributes suitable for pigs, technically making them an option to supplement pigs with farm-grown forages instead of purchased concentrates. A paradox of feeding forages to pigs in Uganda has been identified, though, that suggests a decreasing use potential of forages along a gradient from extensive (mostly rural) to intensive (more urban) smallholder systems, whereas CIAT’s Tropical Forages Program presumes an increasing forage adoption potential along a gradient from subsistence- to marketoriented smallholder systems. Investigating this paradox carefully may help better understand reasons and conditions of smallholders under which cultivated forages may be adopted or not.